Sealing Ability of Resilon as a Root Canal Filling Material: A Systematic Review of In Vitro Studies - Alain Manuel Chaple-Gil; Lazareth Liz Ortiz Santiago; Laura Pereda Vázquez; Meylin Santiesteban Velázquez (Revista Cubana de Medicina Militar)
Objective: This systematic review aimed to evaluate the coronal and apical sealing ability of Resilon, a thermoplastic synthetic root canal filling material, compared to gutta-percha under in vitro conditions.